Lukas ... e as formações imaginárias : uma perspectiva discursiva sobre o político, a política e o voto nas eleições municipais de Maringá - Ragioto, Luis Claudio (2007)
Current research is based on the theoretical presuppositions of the Analysis of the Discourse (AD) of French perspective, keeping as main reference the studies of Michel Pêcheux and Orlandi. Its main objective is to analyze as the images of the politician and of the reader/elector's subject are projected through the discourse political cartoons of Lukas..., a cartoonist of the O Diário do Norte do Paraná newspaper. Considering the theoretical perspective adopted, this paper emphasizes the ideology, discursive formation, discursive memory, imaginary formation and production conditions. Because of the specificities of the corpus, it also contemplates concepts concerning to the relationship among speech, media, politics and humor, besides establishing leaded principles for the discursive analysis of images. As requirement for the analysis, the conditions of production of the political cartoons are considered, they are constituted by the newspaper printed as media support where they are published, by its production process and by the description of the historical-political course about elections in Brazil from the colonization until the Presidential election of 2003, as well as the conditions of production of the elections municipal of Maringá, in the period June - November 2004. The paper presupposes that the one that works is a series of imaginary formations which designates the place where A and B attribute each one to itself and the other; the image that they do from its own position and from the place of the other in the discursive processes. It also presupposes the influence of the media in the process designated as midiatização of the politics and the possible intervention of the television media in other supports, as the newspaper. We understand that this kind of research can, through the memory of facts and of speeches, materialized in words or images, contribute for the constitution of a new way to look of the society for the complex relationships that permeate the speech of the media printed and of the politics, and as these kind of speeches mean in the scope of the humor, through the materiality of the political cartoons.